2019
DOI: 10.1590/s1413-41522019183007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação quantitativa e qualitativa do emprego de paredes como nova perspectiva para captação de água de chuva

Abstract: RESUMO A poluição dos mananciais de abastecimento e a necessidade de se buscar água, cada vez mais distante, agregam à água tratada alto valor monetário, sendo a captação e a utilização da água de chuva uma forma de reduzir custos. Nos grandes centros urbanos, ocorre a formação de ilhas de calor, as quais favorecem a ocorrência de chuvas convectivas dotadas de ventos. Além disso, houve a verticalização das edificações, resultando em área lateral maior, se comparada com a do telhado, tornando a captação de água… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…For this purpose, the parameters of conductivity, turbidity and pH of the rainwater were compared right after it was collected and after it remained 2.5 h inside the covered collector. Thus, it was concluded that the material was inert and could be used in the experiment, as also observed by Marangoni et al (2019).…”
Section: Spatial-temporal Variation In Rainwater Quality and Compliansupporting
confidence: 58%
See 3 more Smart Citations
“…For this purpose, the parameters of conductivity, turbidity and pH of the rainwater were compared right after it was collected and after it remained 2.5 h inside the covered collector. Thus, it was concluded that the material was inert and could be used in the experiment, as also observed by Marangoni et al (2019).…”
Section: Spatial-temporal Variation In Rainwater Quality and Compliansupporting
confidence: 58%
“…In this case, the volume of rainwater discarded should be greater than 8.0 L to allow turbidity to meet the recommended. Thus, as also observed by Marangoni et al (2019), the amount of rainwater to be discarded must be locally assessed, so that its quality is in accordance with NBR 15527 (ABNT, 2007).…”
Section: Variation In the Quality Of Rainwater After Passing Through mentioning
confidence: 90%
See 2 more Smart Citations
“…Research shows that in the future Turkey will be among the countries that will experience water stress [51,53].…”
Section: Daylightmentioning
confidence: 99%